Solitary Fibrous Tumor of Cerebellopontine angle – A case report and review of literature - Dr. Nouha Mahmood Alwani; Dr. Nazima Haider; Fatima, Sohaila; Krishnamoorthi Adiga, Balkur (Tropical Journal of Pathology and Microbiology, 2017)
Solitary fibrous tumor is a rare mesenchymal neoplasm. It is ubiquitious in distribution with majority of the tumors arising within the thoracic cavity. Its categorization has changed many times but we present this case according to latest World Health Organization Central Nervous System tumor blue book classification where it has been grouped with hemangiopericytoma as one entity. We present a case of solitary fibrous tumor in cerebellopontine angle of brain in a 63 year old male. This case highlights the importance of immunohistochemistry markers in making a diagnosis and differentiating it from other mimickers.